Liar's dice : a novel - Faithfull, Juliett (Random House, 2026)
"An astonishing debut about a young teenage girl in 1970s Brazil who is torn away from her twin sister-and who must learn what it means to fight for those she loves when all the odds are stacked against her. Dolores and Mita grow up in rural Brazil in lockstep, speaking their own secret language, leading the carnival parade in matching dresses, even sleeping curled around each other. But when Mita develops a degenerative illness, their parents decide to send her to a hospital in their father's native London. There is no Dolores without Mita and now Mita is gone, with no goodbye and no promise as to when they will see each other again. When the family moves to Rio, the girls' parents aspire to fit in with a glamorous group of expats. They act as if Mita never existed, but Dolores fiercely guards her twin's place in their family. In her stodgy British school, Dolores struggles to learn to read and write-until she meets Andrea, a headstrong girl from the dangerous part of town. As the government cracks down on dissenters, and people disappear, Andrea introduces Dolores to a new side of life-and how to survive it. With her new community, Dolores is willing to do whatever it takes-lie, gamble and steal-to get her sister back and bring her family back together. Set in a country where repression and silence are the fabric of everyday life, Liar's Dice captures the precarious intensity of coming of age in a volatile time and the cost of keeping family secrets. Atmospheric and intimate, Dolores and Mita's story attests to the unbreakable bonds of sisterhood, and the courage it takes to hold fast to love-no matter the cost"-- Provided by publisher.